Effect of irrigation on yield and nutrient uptake of summer sesame (Sesamum indicum) in coastal Orissa - KUNDU, D K; SINGH, RAVENDER (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted at Balipatna block in Khurda district, Orissa during 2003 and 2004 to study the effect of irrigation on yield and nutrient uptake of summer sesame (Sesamum indicum L.), and on the availability of N, P and K in sesame growing soil. Five irrigation treatments included were (i) unirrigated control, (ii) 1 irrigation of 6 cm applied at branching, (iii) 1 irrigation of 6 cm applied at flowering, (iv) 2 irrigations each of 6 cm applied at branching and flowering, and (v) 3 irrigations each of 6 cm applied at branching, flowering and capsule development stage. Irrigation significantly increased seed and straw yields and total uptake ofN, P and K of sesame in both the years. Use efficiency of irrigation water in the summer sesame was maximum when it was supplied at flowering (40.0 to 46.7 kg seedha-cm) than at branching stage (20.8 to 32.5 kg seedha-cm). Profile soil samples collected twice from unirrigated and irrigated plots were analyzed for 2 M KC1 extractable N, Bray & Kurtz 1 extractable P, and 1 N NH,OAc extractable K. Irrigation applied at branching increased availability of 2 MKC1 extractable N by 125% and 1 N NH,OAc extractable K by 3% but decreased availability of Bray & Kurt2 1 extractable P by 10% in the acidic Ultic Haplustalf soil.